Error Analysis on Sentence Structure of EFL Undergraduates in Basic Structure Course - Rosyada, Amrina (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2024)
One of the foundations of understanding English grammar for EFL undergraduates is comprehending the English basic structure. It includes functional grammar based on systemic linguistics and emphasizes spoken and written language operating in different social situations. It is crucial to show how texts work beyond the sentence level, how different texts are structured, and how language varies to suit the purpose of the users. It takes on a descriptive approach and focuses on groups of words that function to make meanings. This study aims to identify students’ errors in developing their sentences. Involved by 72 undergraduates in the second semester at a private university in Jakarta, the study applied a descriptive qualitative research design. With the analysis of the participants’ answers on a 20-question quiz in three assignment sessions, the study identified several errors with diverse findings.